RESTORATIVE JUSTICE AS AN ALTERNATIVE WAY OUTSIDE THE JUDICIARY PROCESS OF CRIMINAL CASE BY FULFILL THE RIGHTS OF THE JUVENILE (CASE STUDY OF DELI SUHANDI JUDICIAL PROCESS - Iwahori Yosafat Iwahori Yosafat (Problematika Hukum, 2015)
The human rights of the Child has been ratified by Indonesia therefore the state is obligated to implement and to maintain the course of the enforcement of the rights of children. Not a few children of Indonesia committed the offense as a whole is not necessarily on their own sense considering themselves still children who are not old enough and qualified in law. However, for any errors or accidents that may inhibit himself even turn off their future because they have to deal with the judicial process. Many of those who have to follow such procedural should be arrested and placed in custody. This kind of procedure is able to cause psychological disturbances against the perpetrators, the criminal child will easily get the stigma from the community around them. the public will be difficult to accept detainees to be in their environment, as well as the condition of the crime of child actors who will also feel less confident they would be desperate, and ultimately make them instead become professional criminals. To that end, the author is interested in researching how the legal protection of the rights of children in conflict with the law, especially with the use of the concept of Restorative Justice to be realized in the juvenile justice process so that the perpetrators of criminal acts that do not need to go through the judicial process that will lead to future impacts.